The influence of managerial attitudes on the competitiveness of organizations - Kasza, Lajos (Acta Carolus Robertus, 2025)
Organizations have longed recognized that in order to solve successive economic problems, the only possible way to stay afloat is to increase their competitiveness. The basic task of senior managers is to make decisons in order to achieve this goal. The question arises in what competencies and abilities the leader must have? With what parameters can this ability be evaluated, how can the effectiveness of their decisions be measured? An overview is given of what factors basically influence the competitiveness of organisations, pointing out the connections between them, using the example of trade. Based on our previous research, partially updating them, I present the effect of managerial attitudes on employee satisfaction and motivations, in a mosaic-like way. I point out that managerial attitudes, their decision-making possibilities, as well as the motivation and satisfaction of employees are fundamentally determined by the culture of their organization.
Keywords: evaluation of managerial attitude; organizational competitiveness; corporate culture